Strategi Pengembangan Portofolio Pembiayaan Mikro di Bank Syariah Indonesia (Studi Kasus BSI Cabang Pembantu Bogor Dramaga Perwira) - Yani, Ahmad; Hubeis, Musa; Suharjo, Budi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
The role of micro, small and medium business (UMKM) in the structure of the Indonesian economy is important and strategic. Conventional and sharia banking support the increase of UMKM through funding, as well as technical and non-technical assistance. The research was taken at Bank Syariah Indonesia (BSI) Bogor Dramaga Perwira Sub-Branch Office (KCP), under supervision of Regional V Jakarta 2 and Bogor Area, with a focus on microfinance. The research objectives were (1) to identify internal and external factors that influence the microfinance portofolio development, (2) to formulate an appropriate strategy to increase the growth of microfinance portofolio and (3) to recommend the development of UMKM according to the existing BSI microfinance scheme. This research based on data and information from PT BSI in the period of 2018-2022 which affect financing performance. Data analyzed using the Internal Factor Evaluation (IFE) and the External Factor Evaluation (EFE) matrix, followed by Strength-Weaknesses-Opportunities-Threats (SWOT) and Quantitative Strategic Planning (QSP) matrixes. The internal factors that become strengths are the pricing of low-cost financing with BSI Kredit Usaha Rakyat (KUR) products, easy requirements, Service Level Agreement (SLA) fast financing processes and sharia-compliant financing agreements. External factors that become opportunities are the large number of UMKM, the public's interest to Islamic banking and many competing banks. Alternative strategies results of SWOT analysis followed by QSP matrix were building partnerships with the micro business community through micro cluster financing, maximizing online marketing and services, and innovating microfinance products.